Design of a pulse generator and shock tube for measuring hearing protector attenuation of high-amplitude impulsive noise - Birch, Robert S.; Gerges, Samir N.; Vergara, Erasmo F. (Applied acoustics, 2003)
The effectiveness of hearing protectors against high amplitude impulse noise levels remains the subject of research with objective testing techniques using acoustic test fixtures offering the only realistic method of providing rapid performance data for protector design and qualification. The work presented in this paper examines a prototype test method based on a shock tube and acoustic test fixture for the evaluation of protectors against high-level impulsive noise where established real ear attenuation at threshold methods would be impractical to apply. The results show that the system is capable of producing controlled repeatable high amplitude pressure pulses of variable duration for testing hearing protection devices in a grazing wave type test. A series of pilot tests illustrate how the system can have a sufficient self-insertion loss to reject flanking noise and allow the measurement of protector attenuations of up to 45 dB with little corruption from flanking noise.